Experimental Validation of Induction Heating as an Energy-Efficient Solution for Concrete Curing - Dong-Jin Kim; Chi-Hyung Ahn (IEEE Access)
In this paper, we propose an innovative, environmentally friendly, and efficient technology for concrete curing through induction heating. This technology is complemented by a comprehensive design methodology aimed at achieving uniform heating across the formwork surface. Induction heating concrete curing is a new approach based on the principle of electromagnetic induction for the purpose of concrete curing, and it offers improved heating efficiency and safety in formwork heating. However, the heating range of the formwork surface is limited depending on the induction heating coil. Thus, we introduce a coil structure derived from evaluations of formwork’s surface temperature distribution through finite element analysis simulations. Heating experiments were conducted on formwork without concrete and formwork with concrete, using a coil designed through simulation. In the experiment without concrete, a uniform temperature distribution was confirmed with a small temperature deviation of 4.28°C. For the experiment with concrete, induction heating experiments and steam curing experiments were conducted at low and room temperatures to compare surface temperature distribution, power consumption, and concrete strength. The experimental results show that room temperature induction heating has 11.39% higher strength and 41.86% less power consumption than low temperature induction heating curing. It also shows 3.51% higher strength and 30.56% less power consumption than steam curing. Room temperature induction heating curing is superior to steam curing in terms of strength and power consumption. Also, although low temperature induction heating curing has lower performance than steam curing, the difference is not significant, so it can be a feasible alternative.